Abundance, Richness, Seasonal and Altitudinal Dynamics of Aquatic True Bugs (Heteroptera) in Mountain Wetlands of Argentina - Scheibler, Erica Elizabeth (2016)
Mountain wetlands provide unique information because their biota is highly specific and contributes significantly to regional diversity. The goals of this study were assessing altitudinal and temporal variation in the distribution of Heteropteran assemblages in mountain wetlands; and studying the phenology of the most abundant species. All stages of Heteroptera and data on environmental variables were collected monthly over one year from five mountain wetlands. A simple community structure, and also a low richness of aquatic true bugs, composed of four Heteropteran families (Corixidae, Belostomatidae, Notonectidae and Gelastocoridae), characterized our ponds. Richness and abundance varied temporally and spatially (p < 0.0001); and increased at higher elevations. Additionally, the highest abundance of cold stenothermal species occurred at the highest altitudes where harsh conditions are prevalent. Ectemnostega (E.) quadrata and S. (T.) jensenhaarupi, both endemic to the Andes region, were the most abundant species. Both these species showed univoltine cycles and overwintered as adults. Biodiversity of the Heteroptera reached maximum values in summer when water temperature increased. Temporal and spatial monitoring studies provide key information on the distribution, diversity, and habitat requirements of Heteropteran species as well as on conservation and management of these vulnerable habitats and species which are faced with climate warming.